Study of inhibitory activity for rhamnolipid produced by Pseudomonas aeruginosa against some types of pathogenic bacteria in vivo - Hani Tawfeeq, Maha; Shaheed Yesser, Buthaynah (Al-Qadisiyah Journal of Pure Science, 2018)
Fifty-one isolates of Pseudomonas spp. were isolated from various sources (pathological clinical cases) and non-pathological (contaminated and uncontaminated soil). Twenty-three isolates were identified as P. aeruginosa. Then two P. aeruginosa isolates (P. aeruginosa PP10 from the clinical case isolates and P. aeruginosa PS16 from the soil isolates) were selected for production and extract the Rhamnolipid. The Rhamnolipid was diagnosed by Thin-layer Chromatography (TLC) and show that the two bacterial isolates produced 3 types of rhamnolipids (mono-, di-rhamnolipid and rhamnolipid A). As well as they diagnosed by High-performance Liquid Chromatography (HPLC). This study also determines the values of minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) for biosurfactants and the results was varied depending on the different type of biosurfactants and type of bacteria with lowest values of MIC and MBC for biosurfactants produced by P. aeruginosa. The inhibitory effects of these biosurfactant that under study against types of bacterial pathogens (S. aureus and P. aeruginosa) with in vivo after making skin injury on back of laboratory mice and contaminated with bacterial pathogens. The clinical symptoms of infection to injured skin emerged after 48 hours. Then mice grouped to treat them with biosurfactants at concentration of 30 milligrams / milliliter produced in this study by two bacterial isolates P. aeruginosa PP10 and P. aeruginosa PS16, resulting in a reduction in the time required for recovery. The results obtained showed the difference in the time required for recovery (depending on the nature of the injury and the type of the microorganism causing the infection), which was cured within 5 days when the concentration was 30 mg /ml of biosurfactant produced by P. aeruginosa P.16, followed by a group of mice that recovered after 6 days when the concentration of 30 mg / ml was used by P. aeruginosa PP10 compared to the control mice which recovered after 12 days for mice groups infected with S. aureus. As for P. aeruginosa infected groups, they were cured after 10 days later when 30 mg / ml concentration was used for biosurfactant produced by P. aeruginosa PS16, followed by a group of mice that recovered after 12 days when the 30 mg / ml of biosurfactant produced by P. aeruginosa PP10. In compared to control group mice that was cured after 17 days. From the results of research, we conclude that rhamnolipid was showed effectiveness against different types of bacteria and reduced time of recovery from infections in vivo.